2011
DOI: 10.1002/ps.2206
|View full text |Cite
|
Sign up to set email alerts
|

Growth variation among Bacillus thuringiensis strains can affect screening procedures for supernatant‐secreted toxins against insect pests

Abstract: Methods of screening Bt collections on the basis of feeding bioassays can be misleading with regards to identifying more promising isolates for biocontrol purposes if physiological differences are not considered. The consequences and implications of these findings for the development of experimental systems that depend on toxicity bioassays to identify alternative Bt strains and entomotoxins with practical applicability have been discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Based on previous studies at laboratory scale [28,31,32], this strain has also shown some promise as a source of useful entomotoxic activity secreted in the SN. The possibility of using the SN of Btt 01 as an alternative source of useful entomotoxins was thus verified by applying the residual liquid fraction of a large-scale fermentation, from the same time used to produce spores, in feeding bioassays.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on previous studies at laboratory scale [28,31,32], this strain has also shown some promise as a source of useful entomotoxic activity secreted in the SN. The possibility of using the SN of Btt 01 as an alternative source of useful entomotoxins was thus verified by applying the residual liquid fraction of a large-scale fermentation, from the same time used to produce spores, in feeding bioassays.…”
Section: Resultsmentioning
confidence: 99%
“…Differences in proteotoxin secretion among isolates during bacterial growth have shown to interfere with the final toxic effects of the respective SNs [28]. It was thus necessary to determine whether a similar temporal regulation also occurred with secretion of low-weight metabolites, such as the β-exotoxins.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To us, however, this process is, in fact, currently ongoing everywhere largely because bacteria are among the fastest evolving organisms on Earth (with generation times in hours), and because Bt's genome changes rapidly through mutation and incorporation of new genes by conjugation, transformation, and transduction. Such a high genetic and physiologic diversity in Bt (the raw material of evolution) was evidenced by significant temporal variation in protein/ insect-toxicity secretion in culture and the presence of alternative toxins among isolates from a single subspecies [8,9]. It is noteworthy that the metabolic expense of producing insecticidal crystal proteins does not seem to significantly alter the fitness of Bt, as suggested by the similar levels of plant-colonization ability shown by strains lacking those ICPs [10].…”
mentioning
confidence: 88%